Middle-to-Upper Palaeolithic site formation processes at the Bordes-Fitte rockshelter (Central France) - Aubry, Thierry (2014)
Transformation in technological patterns associated with the Middle-to-Upper Palaeolithic transition between 50 and 40 ka in Western Europe and their relationship with the Neanderthal and Anatomically Modern Human populations and behaviors are issues that continue to stimulate heated debate. In this article we use the Middle and Early Upper Palaeolithic archaeo-stratigraphic record from the Bordes-Fitte rockshelter (les Roches d'Abilly site, Central France), a Bayesian analysis of the ages obtained by accelerator mass spectrometry radiocarbon on ultrafiltered collagen and by luminescence on quartz and feldspar grains, to establish a timeline for material culture and sedimentary dynamic changes during the Middle-to-Upper Palaeolithic transition. Technology, refitting studies and taphonomy of lithic artifacts recovered in the geoarchaeological field units D1 and D2 permit to characterize 3 reduction strategies (Levallois, Discoidal and Ch^atelperronian blade) that took place between the cold Heinrich events 5 and 4. We discuss the implications of the results to characterize the end of the Middle Palaeolithic, and for distinguishing anthropogenic and non-anthropogenic factors in Middle-to-Upper Palaeolithic assemblage's variability.